"EARLY CHILDHOOD CARIES: UPDATES ON PREVENTION, DIAGNOSIS, AND TREATMENT" (REMUNOM, 2025)
Early Childhood Caries is a multifactorial condition that affects preschool-aged children and represents a public health challenge. This study aims to review the scientific evidence available between 2015 and 2025 regarding strategies for the prevention, diagnosis, and treatment of childhood caries. This is an integrative literature review conducted in the LILACS, PubMed, and ScienceDirect databases. A total of 26 articles that met the eligibility criteria were included. The results showed that early preventive interventions, such as the use of fluoride, sealants, and educational actions for parents and caregivers, significantly reduce the prevalence of the disease. It is concluded that a preventive approach, associated with health education, is essential for controlling early childhood caries, highlighting the importance of multidisciplinary involvement.